2010
DOI: 10.1007/s11145-010-9272-9
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of words, knowledge about words: Dimensions of vocabulary in first and second language learners in sixth grade

Abstract: Despite acknowledging the complex nature of vocabulary knowledge, researchers have rarely investigated the dimensionality of this construct empirically. This study was designed to test a multi-dimensional model of English vocabulary knowledge for sixth-grade students from linguistically diverse backgrounds (n = 584). Participants included language minority students learning English as a second language (L2) and students who learned English as a first language (L1). Students were assessed on 13 reading-based me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
107
2
7

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(130 citation statements)
references
References 49 publications
(73 reference statements)
9
107
2
7
Order By: Relevance
“…Note, however, that this might be considered a problem for most of the tasks in the literature on (derivational and inflectional) morphological awareness (cf. Carlisle, 2000, Singson et al, 2000Kieffer and Lesaux, 2012), involving the transformation of real roots into new derived words by using real suffixes. Therefore, even in those studies, one cannot exclude the contribution of lexical competence on morphological awareness achievement.…”
Section: Discussionmentioning
confidence: 99%
“…Note, however, that this might be considered a problem for most of the tasks in the literature on (derivational and inflectional) morphological awareness (cf. Carlisle, 2000, Singson et al, 2000Kieffer and Lesaux, 2012), involving the transformation of real roots into new derived words by using real suffixes. Therefore, even in those studies, one cannot exclude the contribution of lexical competence on morphological awareness achievement.…”
Section: Discussionmentioning
confidence: 99%
“…Kieffer and Lesaux (2012b) found a direct effect of morphological knowledge on reading comprehension in 952 grade 6 students, controlling for reading vocabulary and word reading fluency and an indirect effect via reading vocabulary but not via word reading fluency. In a further study of the dimensionality of the vocabulary knowledge in these grade 6 students, Kieffer and Lesaux (2012a) demonstrated that vocabulary comprised three separate but related dimensions-breadth, contextual sensitivity, and morphological awareness-for both L2 and L1 learners. They see this as support for the familiar instructional division into knowledge about words (morphological and contextual sensitivity) and knowledge of specific word meanings.…”
Section: Morphological Knowledge and Readingmentioning
confidence: 93%
“…Additionally, this feat was accomplished without the inclusion of vocabulary in the models. It is possible that the morphological knowledge task tapped the vocabulary depth dimension that Kieffer and Lesaux (2012a) found represented by their morphological awareness and contextual sensitivity tasks. In the future it would be important to replicate our study and include receptive and expressive measures of vocabulary breadth and depth.…”
Section: Unique Predictions Of Morphological Knowledge To Reading Commentioning
confidence: 99%
“…For instance, in a study conducted by Carlo et al (2004), monolingual U.S. students scored higher than their bilingual peers on the Peabody Picture Vocabulary Test Revised (PPVT-R). Limbird (2007) found less well-developed vocabulary knowledge among German-Turkish bilingual students in comparison to monolingual German students (see also Kieffer & Lesaux, 2012;Mahon & Crutchley, 2006). Moreover, Verhoeven and Vermeer (2006) reported increasing group differences in vocabulary knowledge from grade 3 to grade 6.…”
Section: Reading Literacy Of Students With Immigrant Backgroundsmentioning
confidence: 99%